Characterization of 2-piperidineethanol and 1-(2-hydroxyethyl)pyrrolidine as strong bicarbonate forming solvents for CO2 capture. (August 2017) - Hartono, A.; Rennemo, R.; Awais, M.; Vevelstad, S.J.; Brakstad, O.G.; Kim, I.; Knuutila, H.K.
Highlights: CO2 solubility in 50 mass% 2-Piperidineethanol (2-PPE) and 40 mass% 1-(2-Hydroxyethyl)pyrrolidine (1-(2HE)PRLD) were measured at 40–120 °C. Density and viscosity were measured at 20–80 °C and fitted to a simply correlation as functions of loading and temperature. Thermal degradation tests show that both solvents are more stable and less corrosive than 30 mass% MEA. The oxidative degradation rate of 1-(2HE)PRLD is lower than that of 30 mass% MEA while 2-PPE degrades much faster. Environmental properties tests have shown that both amines are not toxic and readily biodegradable. Abstract: The solubility of CO2 in the aqueous solutions of 50 mass% 2-Piperidineethanol (2-PPE) and 40 mass% 1-(2-Hydroxyethyl)pyrrolidine (1-(2HE)PRLD) was measured at temperatures from 40 to 120 °C at CO2 loading from 0.04 to 0.8 mol-CO2 /mol-amine. The density and viscosity of unloaded and CO2 -loaded solutions were measured at temperatures between 20 and 80 °C and fitted to simplified correlations. Based on a thermal degradation test, both solvents were found to be more stable and less corrosive than 30 mass% MEA. However, oxidative degradation tests indicate that the 1-(2HE)PRLD degradation rate is lower than that of 30 mass% MEA while 2-PPE degrades much faster. From the environmental aspect, both solvents are found to be non-toxic and biodegradable in fresh water. These experimental data will be used for estimation of the energetic and environmental potential as solvents for CO2 capture.